Unique and cumulative effects of different subtypes of sleep problems on burnout among Chinese nurses - Lin, Ping-Zhen; Lin, Yong-Sen; Wang, Xu; Chen, Lan-Lan; Lin, Yan-Yan; Wu, Bi-Yu (Frontiers in Psychology, 2024)
Objective: To investigate the unique and cumulative associations of different sleep problem subtypes with burnout among Chinese nurses. Methods: A survey was conducted in Quanzhou, China, and a total of 744 nurses were included. Burnout was measured by Maslach Burnout Inventory-Human Services Survey across three dimensions: emotional exhaustion (EE), depersonalization (DP) and low personal accomplishment (PA). Pittsburgh Sleep Quality Index was used to measure 15 types of sleep problems. Binary logistic regression was employed to explore the association between sleep problems and burnout. Results: Prevalence of sleep problems, high EE, high DP and low PA were 43.3%, 6.9%, 23.4% and 63.2%, respectively. Experience of sleep problems significantly increased risk for EE (OR=1.31, 95%CI:1.185-1.436), DP (OR=1.08, 95%CI: 1.023-1.142) and PA (OR=1.09, 95%CI: 1.036-1.146). Of the 15 sleep problem subtypes, “feel too cold” and “have pain” were significant predictors of high EE (OR=3.89, 95%CI: 1.629-9.302; OR=3.00, 95%CI: 1.314-6.827, respectively), and “daytime dysfunction” significantly predicted low PA (OR=1.68, 95%CI: 1.135-2.491). Around 40.9% of nurses had reported more than three subtypes of sleep problems. Experiencing more than three subtypes of sleep problems were significantly associated with an increased risk of DP and PA (ORs range from 2.07 to 2.71). Conclusion: These findings suggested that sleep problems was associated with an increased risk of burnout in nurses, with both unique and cumulative risks. Interventions should focus on the prevention and management of the effects of sleep problems among nurses.